Passamaquoddy materials, Frank G. Speck Papers - Prince, John Dyneley, 1868-1945 (1911)
A 327-page Malecite-Passamaquoddy dictionary. Indian-English, arranged according to English alphabet; also, English-Indian. Based on 1911 collection of Passamaquoddy texts printed in Prince (1921).